Expectation Damages, Divisible Contracts, and Bilateral Investment - Susanne Ohlendorf (University of Bonn, Bonn Graduate School of Economics (BGSE), 2006)
We consider a bilateral trade setting with costless renegotiation and investment by both the buyer and the seller. Whether first best levels of relationship-specific investment can be induced by a simple contract depends on available breach remedies. As demonstrated by Edlin and Reichelstein (1996), a contract specifying an up-front transfer, a quantity and a per-unit price is in general not able to achieve the first best when the breach remedy is expectation damages. We show that this result is due to the linearity of the cost function in their counterexample, and does not extend beyond the linear case. If marginal cost is increasing, then at intermediate prices both parties face the risk of breaching, and the first best becomes attainable.
Keywords: D86; K12; L14; 330; expectation damages; breach remedies; renegotiation; hold-up